Analisis Efisiensi Teknis Usahatani Bawang Merah di Kabupaten Bima-Provinsi NTB Menggunakan Fungsi Froduksi Stochastic Frontier Cobb-Douglas - Muhammad Nursan; Nurtaji Wathoni (Fakultas Pertanian, Universitas Timor, 2021)
Bima Regency is the center for the development and production of the largest shallot commodity in NTB Province. However, the productivity of shallots in Bima Regency still needs to be increased in order to achieve maximum production. The purpose of this study is to analyze the factors that influence shallot farming and to analyze the technical efficiency of farmers in conducting shallot farming. Bima Regency is the research area determined by purposive sampling because it is the center of shallot development in NTB Province. The research data was taken by conducting interviews with 35 respondents who were determined by proportional sampling. Then the data obtained were analyzed using the Cobb Douglas Stochastic Frontier production function approach using the Frontier 4.1 software program. Based on the results of the analysis, it was found that the production factor of the number of seeds, urea fertilizer and labor had a significant effect on the production of shallots at the alpha level of 5 percent while pesticides and KCL fertilizers had a significant effect on the production of shallots at the alpha level of 15 percent. The level of technical efficiency of onion farming in Bima Regency is classified as efficient because it has a value of 0.9569. Farmers can still improve efficiency in onion farming by optimizing the use of superior seeds, labor, balanced fertilizer application, and increasing farmers' skills in adopting innovation and using onion cultivation technology.